Alternative dielectrics for hole selective passivating contacts and the influence of nanolayer built-in charge - Mcnab, S; Yu, M; Al-Dhahir, I; Khorani, E; Rahman, T; Boden, SA; Altermatt, PP; Wilshaw, PR; Bonilla, RS (AIP Publishing, 2022)
Highly passivating, hole selective contacts are required for future high efficiency silicon solar cells. This work investigates selected dielectrics as potential SiOx replacements to act as hole selective contacts. AlOx and SiNx were identified as good candidates due to their low valence band offsets to silicon and proven surface passivation capabilities. Simulated J-V curves show AlOx and SiNx maintain acceptable contact resistivities at thicknesses below 1.4 and 1.7 nm, respectively. The SiOx hole contact was found to become extremely resistive even at thicknesses <1 nm, suggesting that either pinholes dominate conduction, or the band offset parameters differ from those in real TOPCon structures. The passivation of the dielectrics was also simulated, with SiOx outperforming both AlOx and SiNx primarily due to the excellent interface. Additionally, the effect of nanolayer built in charge was investigated. Charges below 1012 q/cm2 were found to have little effect, while negative charges above 1012 q/cm2 resulted in reductions in the contact resistivity and recombination current. The calculated selectivity for a 1.4 nm layer of AlOx was 12.9, while a value of 13.8 was calculated for SiNx at typical intrinsic charge levels.